2015
DOI: 10.1177/1477370815571949
|View full text |Cite
|
Sign up to set email alerts
|

Complaints of rape and the criminal justice system: Fresh evidence on the attrition problem in England and Wales

Abstract: Citation: Hohl, K. & Stanko, E. (2015). Complaints of rape and the criminal justice system: Fresh evidence on the attrition problem in England and Wales. European Journal of Criminology, 12(3), pp. 324-341. doi: 10.1177/1477370815571949 This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent AbstractThe UK has one of the lowest conviction rates for rape in Europe. This article presents unique evidence on the factors that influence the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
172
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(187 citation statements)
references
References 37 publications
14
172
1
Order By: Relevance
“…However, research has consistently shown that rape myths as such exist and that their acceptance by police officers often affects their perceptions of what counts as 'real rape' and promotes victim-blaming attitudes ( Hohl and Stanko, 2015). Jordan (2004) further argues rapesupportive beliefs are consolidated and sustained by a patriarchal and hegemonic police culture that is often manifested in the form of 'macho' and misogynistic attitudes by police officers.…”
Section: Cjs Responses To Stalking and Sexual Violence Victimisation:mentioning
confidence: 99%
“…However, research has consistently shown that rape myths as such exist and that their acceptance by police officers often affects their perceptions of what counts as 'real rape' and promotes victim-blaming attitudes ( Hohl and Stanko, 2015). Jordan (2004) further argues rapesupportive beliefs are consolidated and sustained by a patriarchal and hegemonic police culture that is often manifested in the form of 'macho' and misogynistic attitudes by police officers.…”
Section: Cjs Responses To Stalking and Sexual Violence Victimisation:mentioning
confidence: 99%
“…There is a well-established link between intoxication and sexual offences, with data indicating that in at least 50% of rapes reported to the police alcohol had been consumed by either the victim and/or perpetrator (Abbey et al, 2004). However, the inability of the criminal justice system to effectively deter and respond to sexual violence -particularly in cases involving alcohol -is well documented (Hohl and Stanko, 2015). Accordingly, there is an ongoing need and governmental commitment to develop additional methods for reducing sexual violence (HM Government, 2016), with the use of primary prevention campaigns being one such approach (Stern, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Crown Prosecution Service (CPS) data for 2014/2015 indicate that there were 216 referrals to the CPS from the police for HBVA-related offences, of which 67% resulted in charges being brought and 182 completed prosecutions for HBVA, with 91 (50%) resulting in a conviction. 3 Based on the previous research on the attrition of cases of domestic and sexual violence from reporting to prosecution (Hester 2006, Hohl and Stanko 2015, Hester and Lilley 2017 and indeed evidence that the majority of such victims do not report these offences to the police (see for example, Home Office and Ministry of Justice 2013, Women's Aid 2015, p. 11), we might infer that the annual number of victims in England and Wales affected by HBVA is significantly higher than the 200 or so identified by the CPS figures in [2014][2015]. A Freedom of Information request submitted to every police force in England Wales in 2016, asking how many reports of honour-based violence they had received between January 2011 and August 2016, revealed 7048 reports to police, with most incidents recorded as assaults, threats to kill and kidnap.…”
Section: Introductionmentioning
confidence: 99%